Analysis of the Effectiveness of Government Financial Education Programs in Improving Household Financial Decision - Supardi, Musdalifah Putriami; Goso, Goso; Mustafa, Sri Wahyuny (JURNAL MANAJEMEN MOTIVASI, 2025)
This study analyzes the effectiveness of government financial education programs in improving household financial decisions in North Luwu Regency. Using a quantitative approach with purposive sampling of 100 household heads, data were collected through Likert-scale questionnaires and analyzed using SmartPLS. The results show that financial management, household financial management, and financial literacy have significant positive effects on decisions. Financial literacy also mediates these influences, strengthening the relationship between management practices and decision-making. These findings highlight the need for sustainable mentoring strategies to enhance the program’s impact, encourage responsible financial behavior, and improve the long-term economic well-being of households in the region.